India and the QUAD : Delhi’s Balancing Act? - Tara Kartha (2017)
Last month’s meeting in Manila of officials from India, the United States, Australia and Japan, now referred to in the media as the Quad, has aroused speculation on whether this constitutes an Indian challenge to China. A closer examination of India’s position points to a policy of caution at a time of turbulence in India-China ties.